A chronological catalog of the New World species of Scolopendra L., 1758 (Chilopoda: Scolopendromorpha: Scolopendridae) - Shelley, Rowland M. (Zootaxa, 2006)
Since 1758, 140 names have been erected for, transferred into, or assigned to species of Scolopendra occurring in the New World. One hundred sixteen are from definite, though sometimes vague, type localities; 18 are for nominal species without type localities; three lack standing in nomenclature and are invalid; and three are nomina nuda. To facilitate future studies and determining synonymies, these names are cataloged in chronological order in four listings plus a summary roster of senior names and junior subjective synonyms. Additional rosters cite primary homonyms needing rectification and species needing neotypes — ones with revisitable type localities, ones with unknown or overly generalized type localities that cannot be rechecked, and ones whose type specimens may still exist. The Mexican species, S. robusta Kraepelin, 1903, inadvertently reduced to subspecific status under S. gigantea L., 1758, in a popularized booklet, is returned to full specific status and deleted from Colombia, and S. punctiscuta Wood, 1861, is placed in synonymy under S. heros Girard, 1853, which is deleted from India. Scolopendra sumichrasti Saussure, 1860, & S. olmeca Humbert & Saussure, 1969, are possible synonyms of S. pomacea C. L. Koch, 1847. The synonymy of S. viridilimbata Daday, 1891, under S. polymorpha Wood, 1861, is accepted, and the following established synonymies are confirmed: under S. alternans Leach, 1815 — S. sagraea Gervais, 1837, S. cubensis Saussure, 1860, S. complanata, S. multispinata, & S. grayi, all by Newport, 1844, and S. torquata & S. testacea, both by Wood, 1861; under S. subspinipes Leach, 1815 — S. sexspinosa Newport, 1844, and S. placea & S. lutea, both by Newport, 1845; under S. morsitans L., 1758, S. brandtiana Gervais, 1837, and S. pella Wood, 1861; and under S. viridicornis Newport, 1844, S. punctidens Newport, 1844. The following generic assignments are confirmed: S. lobidens Newport, 1844, in Cormocephalus Newport, 1845; and S. cormocephalina Kohlrausch, 1878, S. longipleura Silvestri, 1895, and S. chilensis & S. pallida, both by Gervais, 1847, in Hemiscolopendra Kraepelin, 1903. Scolopendra viridicornis Newport, 1844, a plausible inhabitant of Guyana, is deleted from Cuba and the Lesser Antilles. The publication date of S. alternans Leach, previously thought to be 1813, is corrected to 1815, and that of S. arthrorhabdoides Ribaut, previously cited as both 1912 and 1914, is established as 1913.